2009
DOI: 10.1902/jop.2009.080559
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Body Mass Index and Periodontitis in the Copenhagen City Heart Study

Abstract: BMI may be inversely associated with clinical AL but positively related to BOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
95
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 32 publications
7
95
2
6
Order By: Relevance
“…[23] Additionally, these findings confirmed the results obtained by Xie (2014) who found the proportion of women with periodontitis in under/normal weight, overweight & obese groups were 50.7%, 64.9% & 83.7%, respectively (p < 0.01). [56] However, finding of other previous studies were in contrast to the finding of our study, they failed to demonstrate significant positive associations between obesity and periodontitis, as measured by probing depth & Clinical Attachment Level (CΑL) [99,100] Risks for the occurrence and progression of gingivitis/periodontitis highly increase during pregnancy. [101] Vogt et al, (2012) reported that, the prevalence of periodontаl disease was 47%.…”
Section: Discussioncontrasting
confidence: 91%
“…[23] Additionally, these findings confirmed the results obtained by Xie (2014) who found the proportion of women with periodontitis in under/normal weight, overweight & obese groups were 50.7%, 64.9% & 83.7%, respectively (p < 0.01). [56] However, finding of other previous studies were in contrast to the finding of our study, they failed to demonstrate significant positive associations between obesity and periodontitis, as measured by probing depth & Clinical Attachment Level (CΑL) [99,100] Risks for the occurrence and progression of gingivitis/periodontitis highly increase during pregnancy. [101] Vogt et al, (2012) reported that, the prevalence of periodontаl disease was 47%.…”
Section: Discussioncontrasting
confidence: 91%
“…As determinant of periodontitis, we used a mean loss of attachment of at least 2.55 mm [27,37,38]. This may not be a precise assessment measure of the disease processes associated with periodontitis, because it only includes evidence of past tissue degeneration and not the current state of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…was reported for the relationship between obesity and periodontitis. 34 Although several studies have reported the relationship between obesity and periodontal disease, 11,[13][14][15][17][18][19][20][21] there is no consensus about which pathophysiological mechanism could explain this relationship. Most findings have come from studies with different methodologies for classifying periodontal disease, or with cross-sectional designs or selected or small samples.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, it is not totally clear what the causal pathway between PD and CVD risk is. 10 Many observational studies have evaluated the association between different levels of periodontal disease and traditional CVRFs, such as obesity or correlated measurements, [11][12][13][14][15][16][17][18][19][20][21] while others have reported some association with diabetes 22 or metabolic disorders. 23,24 Among these studies, most reported an increased odds ratio (OR) for the relationship between obesity and periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation